The Language Learning Strategies Used by Students of Merchant Marine Studies Polytechnics Makassar - Nilam Sari Rustam; Arifuddin Hamra; Sukardi Weda (ELT Worldwide: Journal of English Language Teaching, 2015)
This thesis aims to (1) to investigate the kinds of language learning strategies the merchant marine polytechnics students use in learning English, (2) to investigate the most dominant language learning strategies used by successful and unsuccessful students, and (3) to find out whether or not the successful students employ different language learning strategies from the unsuccessful students. The researcher applied descriptive quantitative method. The population of this research was the students of merchant marine polytechnics of Makassar in academic year 2014/2015.  The  sample  was  the  fourth  semester  students  of  nautical  study program,  class  C  which  consisted  of  30  students.  This  research  used  cluster random sampling technique. This research used 2 kinds of instruments; they were English skill tests and questionnaire. The research data was collected by using English skill tests and SILL questionnaire which were analyzed by descriptive and inferential statistic through SPSS 20.0 for windows program.The result of the descriptive quantitative data showed that (1) the nautical students of merchant marine polytechnics used six kinds of language learning strategies namely metacognitive, compensation, social, memory, cognitive, and affective strategy (2) the most dominantly used language learning strategies among the successful students is metacognitive strategy and the most frequently used language learning strategies among unsuccessful students is social strategy (3) there is a difference in using language learning strategies between successful students and unsuccessful students. The six language learning strategies were employed by the students in learning  English.  The  successful  students  employed  two  kinds  of  language learning strategies; metacognitive and compensation strategy while the unsuccessful students employed four kinds of language learning strategies namely social, memory, cognitive, and affective strategy. Keywords: Language Learning Strategies, Successsful/Unsuccessful Students, Metacognitive, Compensation, Social, Memory, Cognitive, And Affective Strategy